CHRONIC STRESS EXPOSURE AND DAILY STRESS APPRAISALS RELATE TO BIOLOGICAL AGING MARKER P16INK4A IN MID-LIFE PARENTS. (11th November 2018) - Rentscher, K; Carroll, J; Cole, S; Repetti, R; Robles, T
Abstract: Previous research has linked exposure to adverse social conditions such as chronic stress with DNA damage and accelerated telomere shortening, raising the possibility that psychological stress may impact biological aging pathways, ultimately increasing risk for age-related diseases. Less clear, however, is whether this leads to cell growth arrest and cellular senescence. The present study examined daily diary reports of stress appraisals in 73 parents (Mage = 43.0, SD = 7.2; 55% female) over an 8-week period, along with interview-based and questionnaire (Perceived Stress Scale) measures of adverse exposure to and experience of stress, and markers of cellular aging. Participant blood samples were used to assess two markers of cellular aging: gene expression of senescent cell signal p16INK4a (CDKN2A) and leukocyte telomere length. Random effects models covarying for age, sex, ethnicity, and BMI revealed that participants with greater chronic stress exposure during the 6 months prior to study entry (β = .01, p = .04), higher self-reported perceived stress (β = .02, p < .001), and accumulated daily stress appraisals over the 8-week period (β = .01, p = .01) showed increased gene expression of p16INK4a. No significant associations with telomere length were found. Findings extend previous work on the impact of stress on biological aging by complementing traditional measures of stress exposure with assessments of daily experiences and linking these measures to an accumulation of senescent cells. This study supports the hypothesis that chronic stress is associated with accelerated aging by inducing cellular senescence, a common pathophysiology in age-related diseases.